2023
DOI: 10.1159/000534701
|View full text |Cite
|
Sign up to set email alerts
|

Proton Pump Inhibitors and Hyporesponsiveness to Erythropoiesis-Stimulating Agents in Hemodialysis Patients: Results from the Japan Dialysis Outcomes and Practice Patterns Study

Akio Nakashima,
Yoshia Miyawaki,
Hirotaka Komaba
et al.

Abstract: <b><i>Introduction:</i></b> Hyporesponsiveness to erythropoiesis stimulating agents (ESAs) is important problem in dialysis patients. While proton pump inhibitors (PPIs) may inhibit iron absorption, few studies have examined associations between PPIs and ESA-resistant anemia in hemodialysis patients. This study examined the associations between PPIs and ESA-resistant anemia in hemodialysis patients. <b><i>Methods:</i></b> The present study was a cross-sectional s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 49 publications
(68 reference statements)
0
1
0
Order By: Relevance
“…The use of PPI in chronic hemodialysis patients has been associated with many adverse events such as hip fracture, hypomagnesemia, abdominal aortic calcification, and all-cause mortality [ 23 , 24 , 25 , 26 ]. A recent Japanese study has also shown a significant association between the use of PPI and hyporesponsiveness to erythropoiesis-stimulating agents in hemodialysis patients [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…The use of PPI in chronic hemodialysis patients has been associated with many adverse events such as hip fracture, hypomagnesemia, abdominal aortic calcification, and all-cause mortality [ 23 , 24 , 25 , 26 ]. A recent Japanese study has also shown a significant association between the use of PPI and hyporesponsiveness to erythropoiesis-stimulating agents in hemodialysis patients [ 27 ].…”
Section: Discussionmentioning
confidence: 99%